A Study to Assess Dermatoglyphic Characterization and Salivary Ph in Early Childhood Caries: Life Sciences-Health - Kattakayam, Annamary; G. S, Prathima; R, Sajeev; G, Kayalvizhi (International Journal of Life Science and Pharma Research, 2022)
Dental caries detection at an early stage by applying dermatoglyphics and assessing the salivary pH levels can facilitate the initiation of preventive measures at a younger age. However, there are little data available to substantiate the utility of dermatoglyphics and salivary pH in studying the genetic basis of dental caries.Therefore,the present study was aimed to assess the correlation between dermatoglyphic patterns and salivary pH in children with and without Early Childhood Caries (ECC).This cross-sectional study was carried out in 156 children of randomly selected schools in Puducherry in the age group of 3-5 years. Children with decayed, extracted and filled (defs) score of = 5 for group 1 (children with ECC) and defs score of 0 for group 2 (children without ECC) were considered for the study. Their fingerprint patterns and salivary pH were recorded and analysed using Chi-square test and Spearman correlation tests.In children without ECC group, loop frequency 10 and 7 was the most observed category whereas in subjects with ECC group, whorl frequency 7 and 8 was the most observed category. Significant proportion of whorls was seen more in both males and females in ECC group(p<0.0001). The mean salivary pH of subjects with ECC was 6.35±0.38 which was statistically significant (p<0.0001). Dermatoglyphic pattern and salivary pH can be used as predictive tool for diagnosis of ECC as there exists a definite variation in dermatoglyphic patterns and salivary pH in children with ECC and caries-free group. There are various methods to diagnose ECC but so far, there is no method to predict ECC using a dermatoglyphic pattern, salivary pH and ECC that may further facilitate initiation of preventive measures to avoid the progression of ECC at a younger age.